Research and design - Seivewright, Simon (Lausanne, Switzerland : AVA Academia, 2007)
"Research is fundamental to the success of any design-related project and in Research and Design you will discover what research is, why it is so important and where to go for inspiration when developing concepts and themes for your own creative sketchbook. Research and Design crucially shows you how to maximize what you have learnt at the research stage by successfully illustrating, communicating and presenting your design work."--P. [4] of cover.
Research: what and why? : What is a brief? ; What is research? ; What should research contain? ; Who are you designing for? ; Exercise 1. Brainstorming ; Interviews : Alice Palmer; Wendy Dagworthy; Alexander Lamb; Daniel Pollitt -- Choosing what to research : Choosing a theme ; What are primary sources? ; What are secondary sources? ; Sources of inspiration ; Exercise 2. Recycled garment manipulation ; Interviews : Dr. Noki; Richard Sorger -- Compiling your research : The sketchbook ; Techniques for drawing ; Collage ; Juxtaposition and deconstruction ; Cross-referencing ; Analysis of research ; Focus on key elements ; Exercise 3. Focus research pages ; Moodboards ; Sketchbook examples ; Interviews : Omar Kashoura; Jenny Packham -- Designing from your research : Bridging the gap ; Exercise 4. Collaged research on figures ; Model and drape ; Photomontage with drapery ; Design development elements ; Exercise 5. Working with the colour wheel ; Market levels in fashion ; Exercise 6. Design development 1 ; Refinement of individual garments ; Excise 7. Design development 2 ; Selecting ideas to form a collection ; Interviews : WGSN; Julien Macdonald -- Communicating your ideas : Drawing for design ; Templates ; Exercise 8. Creating a design development six-figure template ; Illustrating with collage ; Art materials ; Illustration ; Working drawings ; Layout and composition ; Beyond the drawing board ; Interviews : David Downton; Caryn Franklin -- Glossary.
Originally published in 2007.
This title takes you through the essential stages of research and translation into design ideas. It discusses elements such as the brief and the constraints it can place on the research and design process, and explains the importance of identifying your target market and understanding the different levels and genres of fashion.
Includes bibliographical references (176-177) and index.
Keywords: Fashion design; Fashion design -- Study and teaching